PENGARUH FEE AUDIT DAN MASA PERIKATAN AUDITOR TERHADAP KUALITAS AUDIT - Nuridin; Dista Widiasari (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
This study was conducted to determine the effect of partially or simultaneously between the fee and past audit engagement auditor to audit quality in KAP in Bekasi Region. This research was conducted in the Public Accounting Firm (KAP) in Bekasi. The method used for data collection, through primary data. Data analysis method used is the method of quantitative and qualitative approaches. From the results of the study showed that simultaneous audit fee and the period of the engagement auditor significant effect on audit quality and partial results showed that the variable fee and future audit engagement auditor to audit quality in KAP in Bekasi. As these two factors contribute to variation of quality factor change auditing 79.8%. The conclusion of this study, and a variable fee audit engagement auditor significantly affect audit quality variables either partially or simultaneously. Suggestions from this study, expected variables need to be improved such as competence, experience auditor, audit firm rotation, a public accounting firm's reputation and independence of auditors.